Lightning protection and radio frequency interference mitigation for the Karoo Array Telescope - Wiid, P. Gideon (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhD (Electrical and Electronic Engineering))--University of Stellenbosch, 2010.